THE PROTECTION OF SOCIAL WORKERS IN THE PERSPECTIVE OF THE PRINCIPLES OF HUMANITY AND JUSTICE - Wiryawan, I Wayan Gde (UNISSULA, 2022)
Social problems in Indonesia are so complex. This condition is not matched with the insufficient number of social workers to overcome these social problems. As a result, the social workers experience an overload work. Their jobs are also prone to stress because they have to deal with problems every day. In this research, there are two issues that will be discussed, namely the role of social workers and the tendency of threats to them and protection of the rights of social workers. Social workers are jobs that require expertise and skills to solve problems in relation to legal processes, medical services, spiritual services and so on. In carrying out these jobs, they also tend to experience threats and violences in carrying out their duties. In the concept of the welfare state, the state exists to protect social workers as legitimized in the Law of the Republic of Indonesia Number 14 of 2019 concerning Social Workers. Social workers have the right to legal and labor protection.